2017
DOI: 10.1507/endocrj.ej17-0323
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between bone and glucose metabolism [Review]

Abstract: Abstract.Accumulating evidence has shown that bone and glucose metabolism are closely associated with each other. Since the risk of osteoporotic fractures is increased in patients with diabetes mellitus (DM), osteoporosis is recently recognized as one of diabetic complications, called DM-induced bone fragility. Previous studies showed that collagen cross-links of advanced glycation end products (AGEs) and dysfunctions of osteoblast and osteocyte are involved in DMinduced bone fragility. Circulating levels of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 81 publications
2
46
0
21
Order By: Relevance
“…Similar studies were also reported in type I diabetes mellitus . It has been recommended that skeleton deterioration and fragility, such as osteoporosis, are also part of diabetic‐related complications …”
Section: Introductionsupporting
confidence: 75%
“…Similar studies were also reported in type I diabetes mellitus . It has been recommended that skeleton deterioration and fragility, such as osteoporosis, are also part of diabetic‐related complications …”
Section: Introductionsupporting
confidence: 75%
“…However, overweight and obese patients present an increased risk of fracture to minimal trauma, such as proximal humerus fracture or ankle [10,24], thus an increased BMI is no longer a protective factor against fragility fractures as it was considered in the past [5,12,23,24]. Thereby, the risk of fracture in diabetic patients is less dependent on the bone quantity (bone mass density), but more on bone quality [12,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between D-mannose and bone metabolism is still obscure, accumulating evidences have shown that saccharides, like glucose play a role in bone metabolism. [33][34][35] For example, Kanazawa and colleagues reported that advanced glycation end-products of glucose can increase reactive oxygen species production, impair osteoblast and osteocyte activity, and eventually decrease bone formation. 35 However, as an epimer of D-glucose, D-mannose increased bone formation inversely, which may be associated with other mechanisms.…”
Section: Discussionmentioning
confidence: 99%